2023
DOI: 10.1057/s41310-023-00182-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate governance on financial performance: a cross-sector study

Abstract: Corporate governance remains the focus of current research and a concept that continues to evolve to meet the needs of business managers. Faced with the need for companies to cope with a world characterized by perpetual change and successive economic crises (Prowse in Revue d'économie financière 31:119–158, 1994), the identification of the results of the implementation of good governance mechanisms in the structure of the management of companies on financial performance remains a necessity that helps managers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The findings of the study are consistent with that of Affes and Jarboui (2023), Olokoyo, et al, (2019), Umar and Sanni (2021) and Olani and Berhanu (2015). However, findings from the studies separately conducted by Musa, et, al.…”
Section: Board Size and Return On Assetssupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of the study are consistent with that of Affes and Jarboui (2023), Olokoyo, et al, (2019), Umar and Sanni (2021) and Olani and Berhanu (2015). However, findings from the studies separately conducted by Musa, et, al.…”
Section: Board Size and Return On Assetssupporting
confidence: 90%
“…In Olani and Berhanu (2015) and Firehiwot (2015), it was found that frequency of Board meetings shares a positive relationship with Return on Assets. This finding is contrary to the findings of some researchers such as Affes and Jarboui (2023) and Salim, et al (2016). For this set of researchers, they strongly believe, through their separate results/findings, that just an increase in membership of Board of Directors cannot lead to an improvement in financial performance.…”
Section: Frequency Of Board Meetings and Return On Assetscontrasting
confidence: 72%
“…The close relationship between shareholders and managers in these small firms fosters a culture of stewardship, enabling managers to align their goals with the long-term success of the company (Davis et al 1997), unlike in large public companies where the separation of ownership and control is more pronounced (Bonazzi and Islam 2007). The presence of shareholders as directors and managers may not have a significant impact on financial performance because both groups of managers (with and without shareholder presence) are intrinsically motivated to act responsibly and in the best interest of the company (Affes and Jarboui 2023;Caselli et al 2023). They prioritize the long-term success of the company over personal gains, leading to similar financial performance outcomes regardless of whether shareholders are directly involved in the management roles.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This hypothesis is based on the assumption that partial shareholder-manager alignment in the DM3 group may lead to similar financial performance outcomes as in the DM2 group. Affes and Jarboui (2023) suggest that both groups of managers, regardless of the presence of shareholders, may be intrinsically motivated to act responsibly and in the best interest of the firm, thus minimizing the potential impact of conflicts of interest on financial performance. Consequently, we expect the financial performance of firms in the DM2 group to be comparable to that of firms in the DM3 group.…”
Section: H13mentioning
confidence: 99%
“…To restore investor's confidence, the governance mechanism is systematized to ensure returns on investments. Resulting, some researchers find a positive effect of the internal governance mechanism on a firm's performance (Puni and Anlesinya, 2019), while some find a negative (Affes and Jarboui, 2023). Although, there are numerous studies based on the relationship between governance attributes and their impact on a firm's performance empirical findings and arguments have gone both ways (Sheikh et al, 2013), leading towards different conclusions.…”
Section: Corporate Governance Attributes and Firm's Performancementioning
confidence: 99%